Mau Mau Kenyan emergency 1952-60 - Baxter, Peter (Solihull Helion, 2012)
The Second World War forever altered the complexion of the British Empire. From Cyprus to Malaya, from Borneo to Suez, the dominoes began to fall within a decade of peace in Europe. Africa in the late 1940s and 1950s was energized by the grant of independence to India, and the emergence of a credible indigenous intellectual and political caste that was poised to inherit control from the waning European imperial powers. The British on the whole managed to disengage from Africa with a minimum of ill feeling and violence, conceding power in the Gold Coast, Nigeria and Sierra Leone under an orderly constitutional process, and engaging only in the suppression of civil disturbances in Nyasaland and Northern Rhodesia as the practicalities of a political hand over were negotiated.
Includes bibliographical references.
Keywords: Kenya--History--Mau Mau Emergency, 1952-1960.